2019
DOI: 10.1080/21541264.2019.1698934
|View full text |Cite
|
Sign up to set email alerts
|

The role of enhancer RNAs in epigenetic regulation of gene expression

Abstract: Since the discovery that enhancers can support transcription, the roles of enhancer RNAs have remained largely elusive. We identified that enhancer RNAs interact with and augment bromodomain engagement with acetylated chromatin. Here, we discuss our recent findings and the potential mechanisms underlying the regulation and functions of enhancer RNA-bromodomain associations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 81 publications
0
8
0
Order By: Relevance
“…To help substantiate this premise, the interactome associated with NAC TFs in A. thaliana was analysed. Results indicated that NAC TFs are potentially involved in a least 289 different (1) Fbox domain followed by protein kinase and NAC domain (2) NAC domain followed by G_TR_2 domain (3) RDRP domain followed by NAC (4) NAC domain followed by CHCH domain (5) TPR repeats followed by NAC domain (6) F-box domain followed by NAC and F-box domain (7) NAC domain followed by YJEF_N domain (8) NAC domain followed by HTH domain (9) Homeobox domain followed by NAC domain (10) NAC domain followed by three GH6.2 domain (11) ANK repeat domain followed by NAC domain (12) NAC domain followed by peroxidase domain (13) NAC domain followed by LONGIN and V_SNA domain (14) NAC domain followed by RECA_2 and RECA_3 domain (15) KH_TY repeats followed by NAC domain (16) NAC domain followed by RAB domain (17) JMJN domain followed by NAC domain (18) NAC domain followed by APAG domain (19) two RRM domain followed by NAC domain (20) carrier domain followed by NAC domain and (21) NAC domain followed by DCO domain. The identification of chimeric NAC domain sequences was determined using the ScanProsite and InterProScan server.…”
Section: Nac Tfs Are Involved In Diverse Cellular Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…To help substantiate this premise, the interactome associated with NAC TFs in A. thaliana was analysed. Results indicated that NAC TFs are potentially involved in a least 289 different (1) Fbox domain followed by protein kinase and NAC domain (2) NAC domain followed by G_TR_2 domain (3) RDRP domain followed by NAC (4) NAC domain followed by CHCH domain (5) TPR repeats followed by NAC domain (6) F-box domain followed by NAC and F-box domain (7) NAC domain followed by YJEF_N domain (8) NAC domain followed by HTH domain (9) Homeobox domain followed by NAC domain (10) NAC domain followed by three GH6.2 domain (11) ANK repeat domain followed by NAC domain (12) NAC domain followed by peroxidase domain (13) NAC domain followed by LONGIN and V_SNA domain (14) NAC domain followed by RECA_2 and RECA_3 domain (15) KH_TY repeats followed by NAC domain (16) NAC domain followed by RAB domain (17) JMJN domain followed by NAC domain (18) NAC domain followed by APAG domain (19) two RRM domain followed by NAC domain (20) carrier domain followed by NAC domain and (21) NAC domain followed by DCO domain. The identification of chimeric NAC domain sequences was determined using the ScanProsite and InterProScan server.…”
Section: Nac Tfs Are Involved In Diverse Cellular Processesmentioning
confidence: 99%
“…Some TFs bind to a DNA promoter region located near the transcription start site of a gene and help to form the transcription initiation complex [13][14][15][16]. Other TFs bind to regulatory enhancer sequences and stimulate or repress transcription of the related genes [17][18][19]. Regulating transcription is of paramount importance to controlling gene expression and TFs enable the expression of an individual gene in a unique manner, such as during different stages of development or in response to biotic or abiotic stress [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Transcription of enhancers most likely results from the accumulation of TFs and the consequent recruitment of pol II. However, accumulating evidence over the last decade indicates that at least some eRNAs contribute to enhancer function [8,[14][15][16][17]. Whereas most eRNAs are unstable and rapidly subjected to exosome-dependent degradation, some are more stable and even polyadenylated [11,18], which could underpin their function (Figure 2).…”
Section: Ernas Direct the Actorsmentioning
confidence: 99%
“…Small ncRNAs are less than 30 bp and they include: microRNA (miRNA), short interfering RNA (siRNA), piwi-interacting RNAs (piRNA), tRNA-derived fragments (tRFs), and tRNA halves (tiRNAs). lncRNAs are greater than 200 nucleotides [ 91 , 92 , 93 , 94 ]. With respect to post-transcriptional processing, A-to-I editing has been most studied in miRNAs and lncRNAs [ 32 ].…”
Section: Editing Of Non-coding Rna In Cancermentioning
confidence: 99%